The influence of a 12-week program of physical activity on changes in body composition and lipid and carbohydrate status in postmenopausal women - Pilch, Wanda Barbara; Mucha, Dariusz Mikołaj; Pałka, Tomasz Adam; Suder, Agnieszka Ewa; Piotrowska, Anna Małgorzata; Tyka, Anna Katarzyna; Tota, Łukasz Marcin; Ambroży, Tadeusz (Menopause Review/Przegląd Menopauzalny, 2015)
Introduction: For years there have been studies on what kind of physical activity is optimal for maintaining proper health condition. Besides well known and approved endurance training of moderate intensity, an importance of interval exercise where short term, sudden intensification of work is performed at low endurance load is emphasized. The aim of the work was to assess the effects of a program of physical activity applied to postmenopausal women regarding improvement of their body composition and biochemical indices of lipid and carbohydrate status. Material and methods : The program of physical activity contained 12-week trainings of Nordic walking (NW) and gymnastic-dance classes (G-D). The intensity of effort during the NW training was at the level of 60% HRmax, whereas intensity of G-D exercises was selected based on a subjective assessment of effort according to the scale of American College of Sports Medicine. Results: The 12-week program of physical activity resulted in statistically significant lowering of total cholesterol and low density lipoprotein (LDL) fraction levels. An increase in high density lipoprotein (HDL) cholesterol level was observed, whereas the values of triacylglycerols (TG) did not change. The average fasting blood glucose level decreased significantly. Similar changes were noted for the insulin level. The analysed body biometrical-structural indices did not change significantly. Conclusions : The applied 12-week program of physical activity without changes of dietary habits contributed to an improvement in plasma lipid profile and an increased insulin sensitivity, but it did not affect significantly body composition.